2000
DOI: 10.1016/s0926-9851(00)00017-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 2D VLF data interpretation

Abstract: The ability of the VLF-R (Resistivity) method to provide quantitative subsurface resistivity information is examined. The frequencies used in conventional VLF (15 to 30 kHz) provide the deepest penetrations of the multi-frequency, extended method of RadioMT. Both methods are considered. VLF data, being effectively single frequency, are insufficient to resolve 1D (vertical) structure in any detail. At the site investigation scale, however, it is the departures from the background (vertically uniform) structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…The quantitative interpretation of single frequency VLF-EM data has been investigated by several authors (Beamish 1994(Beamish , 2000Chouteau et al 1996;Kaikkonen and Sharma 1998), who showed that quite detailed information about the subsurface resistivity distribution can be obtained from regularized inversion.…”
Section: Inversionmentioning
confidence: 99%
“…The quantitative interpretation of single frequency VLF-EM data has been investigated by several authors (Beamish 1994(Beamish , 2000Chouteau et al 1996;Kaikkonen and Sharma 1998), who showed that quite detailed information about the subsurface resistivity distribution can be obtained from regularized inversion.…”
Section: Inversionmentioning
confidence: 99%
“…Fortunately, a renovation of VLF-EM interpretation method was developed in the last two decades by adopting new inversion modeling techniques; therefore quantitative interpretation turned out to be possible nowadays. As a result, the VLF-EM survey is capable of yielding more accurate and reliable model of the subsurface structures (Beamish, 1994(Beamish, , 2000Monteiro Santos et al, 2006). However, the success of quantitative interpretation and inversion depends on the quality of the data (Jeng et al, 2007).…”
Section: Review Of the Vlf-em Methodsmentioning
confidence: 99%
“…The reason for this is simply that the regularized inversion scheme attempts to solve the problem of 'equivalence but non-uniqueness' in EM sounding data by constructing a resistivity distribution with the minimum amount of structures that fit the data. In practical application, Beamish (2000) also indicated that single frequency VLF-EM data should be collected at a high lateral density with the intervals of 1 to 5 m to make the inversion more effective, and the degree of smoothing in the inversion should be decreased to reduce the global misfit of the inversion. Moreover, Jeng et al (2007) suggested that the S/N ratio is crucial in the inversion process, and an improperly filtered VLF-EM data may result in false models.…”
Section: Data Inversionmentioning
confidence: 99%
“…Signal penetration is a function of the frequency and material conductivity. For the purpose of landform studies, anthropogenic sources that operate at radio frequencies (radiomagnetotellurics, RMT) or only in the very low frequency (VLF) range of radio signals (Beamish, 2000), are most relevant. At these frequencies depths of penetration are typically on the order of meters to several 10s of meters.…”
Section: Electromagnetic Inductionmentioning
confidence: 99%